2012
DOI: 10.3747/co.19.1151
|View full text |Cite
|
Sign up to set email alerts
|

Extended Adjuvant Temozolomide with cis-Retinoic Acid for Adult Glioblastoma

Abstract: Objective: To determine the toxicity and effectiveness of 24 months of adjuvant temozolomide (TMZ) with cis-retinoic acid (CRA) for patients with glioblastoma. Methods: This retrospective population-based review considered the charts of all patients diagnosed with glioblastoma in Manitoba and referred to a provincial cancer centre during 2002–2008. Consecutive patients came from a population-based referral centre and provincial cancer registry. All patients were treated according to the local standard of care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“… 3 The study by the Manitoba Cancer Center with 116 patients treated with adjuvant temozolomide and cis -retinoic acid for up to 24 cycles or until evidence of disease progression documented 13 patients with elevated transaminases and three cases of elevated bilirubin, but none of these patients discontinued therapy. 10 Our case closely resembles the lethal case of cholestatic hepatitis reported by Sarganas in relation to type of liver injury and the absence of previous liver pathology, 7 but differs regarding the time of onset of liver toxicity: While Sarganas reported the appearance of symptoms at the end of therapy, we observed the start of transaminase elevation after 3 weeks of therapy. The authors reviewed data from the Food and Drug Administration (FDA) adverse event reporting system and recognized seven cases of temozolomide-induced liver injury, but in two cases other drugs potentially responsible for liver toxicity were involved.…”
Section: Discussionsupporting
confidence: 81%
“… 3 The study by the Manitoba Cancer Center with 116 patients treated with adjuvant temozolomide and cis -retinoic acid for up to 24 cycles or until evidence of disease progression documented 13 patients with elevated transaminases and three cases of elevated bilirubin, but none of these patients discontinued therapy. 10 Our case closely resembles the lethal case of cholestatic hepatitis reported by Sarganas in relation to type of liver injury and the absence of previous liver pathology, 7 but differs regarding the time of onset of liver toxicity: While Sarganas reported the appearance of symptoms at the end of therapy, we observed the start of transaminase elevation after 3 weeks of therapy. The authors reviewed data from the Food and Drug Administration (FDA) adverse event reporting system and recognized seven cases of temozolomide-induced liver injury, but in two cases other drugs potentially responsible for liver toxicity were involved.…”
Section: Discussionsupporting
confidence: 81%
“…22 We found that the tumors with high Mcl-1 were significantly correlated with tumors samples with high BNIP3 expression as determined by immunohistochemistry (Fig. 9B, Table 1).…”
Section: Mcl-1 and Bnip3 Co-localize In Glioma Cellsmentioning
confidence: 70%
“…FBW7 has been shown to be important in the degradation of Mcl-1 through the ubiquitination/proteosome pathway. 22 FBW7 has also been shown to be involved in the degradation of HIF-1 23 suggesting it plays a role in eliminating cell survival mechanisms under prolonged hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A third phase II trial evaluating oral all-trans-retinoic acid use in recurrent glioblastoma showed no significant effect on tumor progression or survival [ 51 ]. Of patients receiving CRA along with temozolomide during the initial treatment of glioblastoma, none had improved progression-free or overall survival compared to those receiving temozolomide alone [ 52 ]. There is one ongoing clinical trial evaluating whether isotretinoin can help control glioblastoma when given with temozolomide (NCT00555399).…”
Section: Resultsmentioning
confidence: 99%